2022
DOI: 10.1002/mnfr.202100897
|View full text |Cite|
|
Sign up to set email alerts
|

Whole Agrocybe cylindracea Prevented Obesity Linking with Modification of Gut Microbiota and Associated Fecal Metabolites in High‐Fat Diet‐Fed Mice

Abstract: Scope: Whole-food-based strategies to prevent metabolic diseases are growing interests. Agrocybe cylindracea (AC) is a major edible mushroom with high values of nutrition, but little is known about its health benefits as a portion of whole food. Methods and Results: Diet-induced obese, C57BL/6J mice are fed an high-fat diet (HFD) with or without AC (3% or 5%, w/w in the diet) for 9 weeks. The results show that dietary AC reduced body weight, adipose accumulation, impairment of glucose tolerance, lipid levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…A growing body of research has demonstrated that edible mushrooms and their extracts can ameliorate obesity [ 19 , 20 ]. Consistent with findings in prior studies, adding whole Agrocybe cylindracea [ 5 , 19 ] and Pleurotus ostreatus [ 21 ] to the diet of mice fed a HFD resulted in decreased weight gain and liver weight in a manner that depended on the dosage. Conversely, a study found that consuming a combination of Japanese mushrooms at levels of 0.5% and 3% in a HFD did not lead to a significant reduction in the body weight of mice, similar to LH, but did result in a decrease in the weight of white adipose tissue and perinephric adipose tissue [ 22 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A growing body of research has demonstrated that edible mushrooms and their extracts can ameliorate obesity [ 19 , 20 ]. Consistent with findings in prior studies, adding whole Agrocybe cylindracea [ 5 , 19 ] and Pleurotus ostreatus [ 21 ] to the diet of mice fed a HFD resulted in decreased weight gain and liver weight in a manner that depended on the dosage. Conversely, a study found that consuming a combination of Japanese mushrooms at levels of 0.5% and 3% in a HFD did not lead to a significant reduction in the body weight of mice, similar to LH, but did result in a decrease in the weight of white adipose tissue and perinephric adipose tissue [ 22 ].…”
Section: Resultssupporting
confidence: 88%
“…There are now almost 2 billion overweight adults in the world, and this trend continues to worsen, making obesity a global epidemic [ 3 ]. Obesity and its aggravation of a number of major diseases have become an issue of public health threat, which negatively impacts the quality and longevity of human life and the cost of healthcare [ 4 , 5 ]. Thus, it is a major challenge for us to prevent or ameliorate obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-Diversity analysis is used to evaluate the similarity of the community structure between different groups ( 29 ). Principal co-ordinate analysis (PCoA) and non-metric multidimensional scaling (NMDS) analysis were used to represent community changes in different samples.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing body of evidence suggests that gut flora is associated with the development of obesity and associated metabolic diseases (Torres-Fuentes et al 2017 ; Zhu et al 2022 ). Gut flora is closely associated to host food digestion, nutrient absorption, energy metabolism, and central appetite, which are all associated with obesity (Wijdeveld et al 2020 ).…”
Section: Gut Microbiome In Cmd: Altered Composition Of Gut Microbiotamentioning
confidence: 99%